Managing Inequality: Manager-Specific Wage Premiums and Selection in the Managerial Labor Market - He, Alex Xi; le Maire, Daniel (The Review of Economics and Statistics, 2025)
This paper uses a manager-firm-worker matched dataset covering the entire Danish population to identify manager effects on worker wages. We show that manager-specific wage premiums are almost as important as firm-specific wage premiums in explaining betweenfirm wage inequality. Managers who pay higher wages are more likely to be replaced through acquisitions. Manager-specific wage premiums are uncorrelated with productivity and seem to stem from managers' traits and fairness views. Our results highlight the role of managers in understanding between-firm wage inequality and suggest that the managerial labor market tends to select low-paying managers and redistribute wealth from workers to shareholders.